The Role of Peer Influence on Oral Health Knowledge and Behaviors among Adolescents - Sadeghipour Roudsari, Maryam; Shariatpanahi, Seyed Peyman; Namdari, Mahshid; Khoshnevisan, Mohammad Hossein; Malek-Mohammadi, Mahsa; Foroughmand, Mohammad Hadi (UI Scholars Hub, 2021)
Although many researchers, in different social sciences fields, are being attracted to the new potential promotional phenomenon, the influence of peer connections, the literature in dental public health is very poor. Objective: This article investigates the role of peer influence on individuals’ oral health knowledge and behavior among adolescents. Methods: The purpose of the study was to explore the correlation between secondary school students’ oral health u and knowledge within friendship groups. A valid and reliable questionnaire was developed. A total of 421 students (228 boys and 193 girls) aged between 12-13 years old participated in the study. Ordinal regression analysis was used to identify the correlation between an individual’s oral health knowledge and his/her friends. Results: The results demonstrated a strong relationship between students’ oral health behaviors and their peer connections within their friendship groups at school. Specifically, the tooth brushing frequency of a student had a strong correlation with the similar behavior of his/her friends. Also, investigation of the role of the second level connections (friends of one’s friend with no direct connection) showed a significant correlation in brushing behavior. However, the results revealed no strong correlation of oral health knowledge among friends within their social network. Conclusion: This paper highlighted the importance of the role of peer influence on oral health behavior. Understanding the relationship between oral health behavior and social network would help policymakers for more cost-effective oral health promotion programs among adolescents.